The Problem of Early Marriage in Larangan Perreng VillagePragaan District, Sumenep Regency - Moh. Thayyib; Bagus Amirullah; Dani Samdani (HISTORICAL: Journal of History and Social Sciences, 2024)
Each stage of an individual is faced with a crisis that is a unique developmental task to be resolved. Crisis is not a catastrophe but a turning point characterized by increasing vulnerability and potential that a person has, the more the individual successfully resolves the crisis he faces, the healthier the individual's development. in developing countries, marriage is often used as a sign that someone has entered adulthood. While the fact is that individuals who undergo early marriage have no signs of maturity at all. This happens in our village of Larangan Perreng where children who are still at an early age who are married often do not signify what Arnett has stated in John W. Santrokch's book entitled “Life-Span Development”. This research uses a qualitative approach, with a case study type. The data were collected by interview, observation, and documentation, then the data were analyzed with an interactive data analysis cycle. In testing the validity of the data, triangulation was carried out. The conclusions obtained include, among others, there are two factors in the emergence of problems in the households of residents who married at an early age in Larangan Perreng Village, Pragaan District, Sumenep Regency including, a. Parental interference. b. The emergence of childishness. And there are several impacts of early marriage that occurs in the village of Larangan Perreng Pragaan District Sumenep District, among others, a. Impact on social relations, b. Impact on education, c. Impact on mental